A frequent PNPLA3 variant is a sex specific disease modifier in PSC patients with bile duct stenosis - Friedrich, Kilian; Rupp, Christian; Hov, Johannes Roksund; Steinebrunner, Niels; Weiss, Karl Heinz; Stiehl, Adolf; Brune, Maik; Kloeters, Yvonne; Schaefer, Petra; Schemmer, Peter; Sauer, Peter; Schirmacher, Peter; et al. (PLOS ONE, 2013)
Background & Aims Primary sclerosing cholangitis predominantly affects males and is an important indication for liver transplantation. The rs738409 variant (I148M) of the PNPLA3 gene is associated with alcoholic and non-alcoholic liver disease and we evaluated its impact on the disease course of PSC. Methods The I148M polymorphism was genotyped in 121 German PSC patients of a long-term prospective cohort and 347 Norwegian PSC patients. Results In the prospective German cohort, actuarial survival free of liver transplantation was significantly reduced for I148M carriers (p = 0.011) compared to wildtype patients. This effect was restricted to patients with severe disease, as defined by development of dominant stenosis (DS) requiring endoscopic intervention. DS patients showed markedly decreased survival (p = 0.004) when carrying the I148M variant (I148M: mean 13.8 years; 95% confidence interval: 11.6-16.0 vs. wildtype: mean 18.6 years; 95% confidence interval: 16.3-20.9) while there was no impact on survival in patients without a DS (p = 0.87). In line with previous observations of sex specific effects of the I148M polymorphism, the effect on survival was further restricted to male patients (mean survival 11.9 years; 95% confidence interval: 10.0-14.0 in I148M carriers vs. 18.8 years; 95% confidence interval: 16.2-21.5 in wildtype; p<0.001) while female patients were unaffected by the polymorphism (p = 0.65). These sex specific findings were validated in the Norwegian cohort (p = 0.013). Conclusions In male PSC patients with severe disease with bile duct stenosis requiring intervention, the common I148M variant of the PNPLA3 gene is a risk factor for reduced survival.